Evolução da mortalidade de motociclistas em acidentes de trânsito no Brasil - Chaves Filho, Wilson Ferreira (Universidade Federal de São Carlos, 2020)
Between 2000 and 2012, 177 thousand indemnities were paid for the death of motorcyclists and 781 thousand for permanent disability in Brazil. These figures show that studies in this field are necessary in order to understand the general situation and mitigate the damages of the use of this means of transportation that continues to grow in Brazil. This study, regarding the national scenario, used morbidity and mortality numbers provided by the Ministry of Health through a database called DATASUS, population data from the IBGE (Brazilian Institute of Geography and Statistics) and fleet data provided by DENATRAN (Traffic National Department). With this data, the desired indexes were calculated to each region and state in Brazil. To get to other countries indexes, data from WHO reports were used, to show the mortality of motorcyclists in traffic accidents in those countries. It was noticeable the significant increase of the mortality of motorcyclists in Brazil, during the analyzed period, just presenting an apparent stability from 2012. It was also noted that the Northeast region is a problematic one in this respect, presenting the highest rates both in relation to the population and in relation to the fleet for the last year analyzed (2016). The Southeast region had the lowest rates not only in 2016, but throughout the analyzed period. When comparing the Brazilian indexes to the indexes of other economic similar countries (between 2006 and 2016), it was clear that the Brazilian ones are usually higher, when these other countries were the ones that had reached a high income level in the established period. It was also observed a tendency for the motorcycle to be more present in the country's fleet when it has a lower income.
Evolution of motorcycle mortality in traffic accidents in Brazil
Keywords: Motocicleta; Segurança viária; Mortalidade no trânsito; Acidentes de trânsito; Brasil; Motorcycle; Road safety; Mortality in traffic; Traffic accidents; Brazil; ENGENHARIAS::ENGENHARIA DE TRANSPORTES::PLANEJAMENTO DE TRANSPORTES